Régimen disciplinario sancionatorio policial y la aplicación de las garantías constitucionales al debido proceso - Castro Vásquez, Ecuador Gustavo (2021)
The legal framework of civilizations is always changing and the law itself always evolves; this time we find ourselves with the analysis of a new regulatory body such as the Organic Code for Public Safety and Public Order Entities in its first volume, which governs, regulates and monitors not only the organizational structure of the National Police of Ecuador but also its servants’ actions in relation to the intrinsic discipline of our institution. Thus, with the law-making mentioned above, it is important to note that it can be improved at all times. Therefore, through scientific research guided by law, doctrine, jurisprudence and quantitative and qualitative field study, it will be possible to establish that the creation of new legal categories arising from administrative acts is essential for the guarantees under the principle of due process.........